1999
DOI: 10.1002/(sici)1097-0142(19990701)86:1<149::aid-cncr21>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid carcinoma in children and adolescents in ukraine after the Chernobyl nuclear accident

Abstract: BACKGROUND The increase in the number of childhood thyroid carcinoma cases in Ukraine after the Chernobyl nuclear accident in 1986 prompted the development of a registry of thyroid carcinoma cases at the Institute of Endocrinology and Metabolism in Kiev. In the current study, the authors report the statistical data and clinicomorphologic features of the cases included in this registry. METHODS To study the incidence, and age and gender distribution of thyroid carcinoma in Ukraine, the authors compiled complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
99
0
10

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(117 citation statements)
references
References 7 publications
8
99
0
10
Order By: Relevance
“…It is interesting to note that increased levels were especially linked with PTC characterized by lymph node metastases and more aggressive behavior (40) and patients over the age of 45 (41). Again, post-Chernobyl PTC appeared more aggressive at presentation with lymph node metastasis (60-80%); other extrathyroidal spread and venous invasion were commonly observed (11)(12)(13). Our experimental design allowed us to compare the gene expression levels in the two groups characterized by aggressive behavior.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that increased levels were especially linked with PTC characterized by lymph node metastases and more aggressive behavior (40) and patients over the age of 45 (41). Again, post-Chernobyl PTC appeared more aggressive at presentation with lymph node metastasis (60-80%); other extrathyroidal spread and venous invasion were commonly observed (11)(12)(13). Our experimental design allowed us to compare the gene expression levels in the two groups characterized by aggressive behavior.…”
Section: Figmentioning
confidence: 99%
“…A solid papillary histological type was found in 93% of children in the Ukraine (8), and an increased prevalence of ultrasonographic thyroid abnormalities (nodules, cysts) was found (9,10). The tumors appeared to be more aggressive at presentation with lymph node metastasis in 60-80% of patients; other extrathyroidal spread and venous invasion were commonly observed (11,12). The tumors were shown to be more frequently associated with thyroid autoimmunity and developed after a short latent period of 4-5 years (13).…”
Section: Introductionmentioning
confidence: 99%
“…In Belarus, Northern Ukraine and parts of the Russian Federation, about 2000 cases of thyroid carcinoma can be attributed to exposure to fallout; nearly all are papillary carcinomas, and together they form the largest number of cases of cancer of a single type due to a known cause on a known date that have ever occurred (Williams, 2002). The cases vary in their age at exposure and latency; although over 95% of the cancers are classified as papillary carcinomas, they vary also in their morphology, ranging from a solid immature phenotype, lacking typical architectural differentiation and with limited thyroglobulin content, to welldifferentiated tumours dominated by either papillary or follicular architecture (Furmanchuk et al, 1992;Nikiforov and Gnepp, 1994;Bogdanova et al, 1995;Williams, 1996;Tronko et al, 1999). Many tumours contain a mixture of different patterns.…”
mentioning
confidence: 99%
“…In reality they were even somewhat smaller" or "Tumors with a shorter latent period show more pronounced intra-and exrtathyroid spread. " (20) In a later study (32), the following figures were reported in regard to TNM staging of TC in children younger than 14 years diagnosed in Ukraine (Table I). It can be seen from the table that the stage T4 was diagnosed in about 50 % of all 244 post-Chernobyl pediatric TC cases.…”
Section: öZmentioning
confidence: 92%
“…It can be seen from the table that the stage T4 was diagnosed in about 50 % of all 244 post-Chernobyl pediatric TC cases. During the years 1981-1985 preceding the accident, only 3 TC were diagnosed in children, all T2 stage (32). To grow to a T4 stage, a tumor needs certain time.…”
Section: öZmentioning
confidence: 98%